2016
DOI: 10.1007/s10803-016-2768-7
|View full text |Cite
|
Sign up to set email alerts
|

Learning with Technology: Video Modeling with Concrete–Representational–Abstract Sequencing for Students with Autism Spectrum Disorder

Abstract: The purpose of this study was to determine the effectiveness of a video modeling intervention with concrete-representational-abstract instructional sequence in teaching mathematics concepts to students with autism spectrum disorder (ASD). A multiple baseline across skills design of single-case experimental methodology was used to determine the effectiveness of the intervention on the acquisition and maintenance of addition, subtraction, and number comparison skills for four elementary school students with ASD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 29 publications
3
35
0
1
Order By: Relevance
“…All of the studies included in the review employed instructional strategies that have been shown to be effective in teaching academic skills, including mathematics, to students with MSD (Browder et al, 2008; Hudson, Browder, & Wood, 2013; King, Lemons, & Davidson, 2016; Spooner et al, 2012). However, findings indicated that researchers are increasingly examining instructional approaches that have been found to be effective in teaching mathematics to students without disabilities including the use of the CRA instructional approach, schema-based instruction, anchored instruction, and the use of technology (Bottge et al, 2003; Jitendra et al, 2012; NCTM, 2000; What Works Clearinghouse, 2012; Yakubova et al, 2016). This is a promising finding because it shows that researchers are becoming more cognizant of the need to teach the conceptual processes that undergird the successful use of mathematics in day-to-day activities including problem solving, reasoning and proof, communicating mathematical ideas, making mathematical connections, and representing mathematical ideas (NCTM, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…All of the studies included in the review employed instructional strategies that have been shown to be effective in teaching academic skills, including mathematics, to students with MSD (Browder et al, 2008; Hudson, Browder, & Wood, 2013; King, Lemons, & Davidson, 2016; Spooner et al, 2012). However, findings indicated that researchers are increasingly examining instructional approaches that have been found to be effective in teaching mathematics to students without disabilities including the use of the CRA instructional approach, schema-based instruction, anchored instruction, and the use of technology (Bottge et al, 2003; Jitendra et al, 2012; NCTM, 2000; What Works Clearinghouse, 2012; Yakubova et al, 2016). This is a promising finding because it shows that researchers are becoming more cognizant of the need to teach the conceptual processes that undergird the successful use of mathematics in day-to-day activities including problem solving, reasoning and proof, communicating mathematical ideas, making mathematical connections, and representing mathematical ideas (NCTM, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Stroizer, Hinton, Flores and LaTonya (2015) used a CRA methodology to teach addition and subtraction involving regrouping and numerical facts involving multiplications to three students with ASD improving their conceptual comprehension of these operations. The work by Yakubova, Hughes and Shinaberry (2016) has shown the effectiveness of a video modeling intervention with CRA instructional sequence when teaching mathematics concepts to students with ASD. Some other intervention studies have successfully used virtual and concrete manipulatives to teach students with ASD arithmetic facts (Bouck, Satsangi, Doughty, & Courtney, 2014) and problem solving (Root, Browder, Saunders, & Lo, 2016).…”
mentioning
confidence: 99%
“…Previous and current research reviews have indicated the effectiveness of video instruction for learners with an autism spectrum disorder on a variety of target skills including socialcommunication (Green et al 2017;Lee et al 2017;Macpherson et al 2015;Shukla-Mehta et al 2010), daily living (Mechling et al 2015), academic (Yakubova et al 2016), vocational (Seaman and Cannella-Malone 2016), and recreational skills (Sherrow et al 2016).…”
Section: Historical Backgroundmentioning
confidence: 99%